¡Nunca más un México sin nosotros! : um estudo sobre as novas representações do indígena construídas pelo movimento zapatista mexicano (1994-1996) - Nigri, Sarah Domingues da Rocha (2009)
Discourses and new social representations which are produced by social movements, certainly, play an important role in their fights because these representations carry meanings that can change or keep the power relations present on the society. Many times, the most important demand of excluded groups is demonstrating their conditions of worthy people with specific rights. In México, the “Ejército Zapatista de Liberación Nacional” tries to re-mean and rebuilt the indigenous identity and intend to modify the negative representations about the “Indian” which is divulged in Mexican society. Analyzing discourses produced by zapatists during the first three years after the armed insurrection on January, 1994, it is possible to conclude that one of the most important resistance strategies used by zapatists in Chiapas is substituting a “negative image” of “Indian” for a “positive representation” of “Indianity”. The objective of this work is discussing and analyzing the symbolic dimension of the zapatist resistance and identifying the new representations about “Indian” produced by zapatist movement which intend to became the “Indians” symbols of dignity and examples of resistance in fights against oppression, exploration and forgetfulness.